Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada PT Pelabuhan Indonesia (Persero) Regional II Palembang - Maudia, Tara Indah; Mafra, Nisa Ulul; Darmawati, Tri (Peneliti.net, 2023)
This study aims to determine the effect of individual characteristics and work environment on employee performance at PT Pelabuhan Indonesia (Persero) Regional II Palembang. The population in this study were 70 employees of PT Pelabuhan Indonesia (Persero) Regional II Palembang and the sample taken was 70 employees using a saturated sample. The data analysis technique used in this study is multiple regression analysis, coefficient of determination (R2), t test (partial) and f test (simultaneous). Based on the data analysis conducted, this study found that by means of the t test individual characteristics affect employee performance with a value of 0.000 ˂ 0.005 and the work environment does not partially affect employee performance with a value of 0.616 ˃ 0.05. The results of the F test (simultaneous) obtained a value of 0.000 ˂ 0.05, which means that H0 is rejected and H1 is accepted so that it can be concluded that there is an influence of individual characteristics and work environment on employee performance at PT Pelabuhan Indonesia (Persero) Regional II Palembang. The coefficient of determination (R2) is 0.500 or 50% and the remaining 50% is influenced by other factors that may not be included in this study such as workload, work motivation and others. Keywords: Individual Characteristtics ; Work Environment ;Employee Performance